Efektivitas Perangkat Pembelajaran Berbasis Flipped Classroom untuk Meningkatkan Kemampuan Penalaran Matematis Peserta Didik - Ridia Fedistia; Edwin Musdi (Universitas Syiah Kuala, 2020)
This study was aiming at determining the impact of mathematics learning instruments based on flipped classroom in improving students' mathematical reasoning abilities. This is development research adapting the Plomp development model. This research was conducted in three stages: preliminary research, prototyping phase, and assessment phase. The subjects of this study were students one of the senior high schools in Padang, Indonesia. The instrument used was a test of mathematical reasoning ability. Data were analyzed by quantitative methods. The results showed the number of students achieving the minimum criteria of mastering learning concerning mathematical reasoning ability, increasing from 47.22% to 75%. The mathematical reasoning ability of students in groups increased from the first to the fifth meeting, and the level of implementation of learning by the teacher was in a good category. This means that the learning tools based on Flipped Classroom were effective in improving students' mathematical reasoning abilities.